THE HIERARCHY OF NEEDS OF LOUISA CLARK IN ME BEFORE YOU NOVEL - Sitepu, Juni Clara; Putri, Aulia (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
The writers described hierarchy of human needs and what are dominant needs of Louisa Clark base on Maslow’s theory. The writers are interested to discover the psychological needs, the needs for security, the needs for love and belonging, the needs for esteem and self-actualization needs of Louisa Clark in 'Me Before you' novel by the famous novelist Jojo Moyesn based on Maslow’s theory. This research is qualitative research. In the data collection technique, the writers use a descriptive textual method. In the process of analyzing the data, the writers collect the data and then the data are rewritten and grouped by the types. Then the data are analyzed again based on the theory of 'Hierarchy of Human Needs by Abraham Maslow'. The result of analyzing data is Louisa Clark needs all needs in Maslow’s theory. In conclusion, from five Maslow’s human needs theory the dominant needs needed by Louisa Clark is love and belonging needs.